2010
DOI: 10.3746/jkfn.2010.39.3.383
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study on Middle School Students of Gwangju and Jeonnam in Terms of Dietary Behavior, Body Perception and Weight Control Concerns According to BMI

Abstract: This study was performed to investigate the food habits, eating behaviors, perception of body shape, statuses of body weight control by BMI (Body Mass Index) of 732 middle school students in Gwangju and Jeonnam. The results of this study were compared among under weight (UW), normal weight (NW), and overweight (OW) groups according to BMI levels. In the OW group, female students had low scores in eating at night only, while male students had low scores in eating at night, eating speed, and food selection. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
2
6
1
Order By: Relevance
“…About 60% of the students were determined to have normal weight according to the BMI, while 30% and 11% of them were underweight and overweight, respectively. These results differed from other previous researches [ 1 - 3 , 31 , 35 ]. The most similar results were those of Kang and Lee [ 3 ], which showed that 54% of students were normal weight, 37% underweight, and 10% overweight and obese.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…About 60% of the students were determined to have normal weight according to the BMI, while 30% and 11% of them were underweight and overweight, respectively. These results differed from other previous researches [ 1 - 3 , 31 , 35 ]. The most similar results were those of Kang and Lee [ 3 ], which showed that 54% of students were normal weight, 37% underweight, and 10% overweight and obese.…”
Section: Discussioncontrasting
confidence: 99%
“…The most similar results were those of Kang and Lee [3], which showed that 54% of students were normal weight, 37% underweight, and 10% overweight and obese. Inconsistency with the results of other studies might be due to regional differences in sampling [1-3,35] or methodological differences [31]. This study calculated the BMI based on self-reported information, while the Korean Ministry of Education, Science and Technology [31] used direct measurements of height and weight.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The nine independent variables were as follows: student's grade level, body mass index (BMI), family affluence scale as a representation of household income level, average spending money per week, household members, perceived body image, effort towards changing body weight during the last month, stress awareness, and research year. In addition to the demographic factors and variables of direct interest to this study, other variables were mostly selected based on the factors reported in previous research to be associated with adolescents' eating habits [ 14 , 15 , 21 ]. The average amount of spending money per week was also chosen as one of the independent variables in order to examine the effect of being able to afford consuming meal substitutes, such as fast foods or other snacks.…”
Section: Methodsmentioning
confidence: 99%